Age of discovery English, French & Dutch explorations - Coronet/MTI Film and Video ([Deerfield, IL] Coronet/MTI, 1979)
Uses artwork, map animation, and scenic photography to trace the routes taken by English, French, and Dutch explorers and analyzes the effects of their expeditions.
Distributed by International Book Center.
Keywords: Discoveries in geography; America -- Discovery and exploration